Transformasi Peran Guru PAI dalam Pembentukan Kesadaran Beragama Siswa di Era Digital: Studi Implementatif di SMP Negeri 5 Cilacap - Kahfi, Rofiul; Azis, Donny Khoirul (Jurnal Alwatzikhoebillah : Kajian Islam, Pendidikan, Ekonomi, Humaniora, 2026)
The digital era has significantly shaped students’ behavior and religious orientations, posing new challenges for religious education. This study examines the transformation of the role of Islamic Religious Education (PAI) teachers in fostering students’ religious awareness at SMP Negeri 5 Cilacap. A qualitative descriptive approach was applied, with data collected through interviews, classroom observations, and document analysis involving PAI teachers and students. Data were analyzed using an interactive model, supported by triangulation of sources and methods. The findings indicate that PAI teachers’ roles have shifted from conventional instruction to multifaceted functions, including mentoring, motivating, facilitating, and serving as exemplary role models. This transformation is realized through habituation of religious practices, exemplary conduct, and sustained guidance, contributing to the development of students’ religious awareness across cognitive, affective, and behavioral dimensions in the digital era.